The Global Atlas for Siting Parameters project: Extreme wind, turbulence, and turbine classes. Issue 11 (15th August 2022) - Larsén, Xiaoli Guo; Davis, Neil; Hannesdóttir, Ásta; Kelly, Mark; Svenningsen, Lasse; Slot, René; Imberger, Marc; Olsen, Bjarke Tobias; Floors, Rogier
Summary: The Global Atlas for Siting Parameters project compiles a suite of models into a complex modeling system, uses up‐to‐date global datasets, and creates global atlases of siting parameters at a spatial resolution of 275 m. These parameters include the 50‐year wind, turbulence, and turbine class recommendations based on relevant generic turbines. The suite of models includes the microscale Linear Computational Model (LINCOM), a statistical, spectral correction method here revised for strong convective areas and tropical cyclone affected areas, two turbulence models with four setups, and load models. To this complexity, an uncertainty model was developed to classify the various sources of uncertainties for both the extreme wind and the turbulence calculations, and accordingly, atlases of uncertainty classification were created. Preliminary validation of the global calculations of the 50‐year wind and turbulence is done through comparisons with measurements, and the results are promising. This is the first time the siting parameters are obtained with such a high spatial resolution and shared on open data portal. It is expected to benefit the global wind energy planning and development.